2021
DOI: 10.1021/acsaem.1c02337
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Ion Battery Anode of Mesocrystalline CoTiO3/TiO2 Nanocomposite with Extremely Enhanced Capacity

Abstract: Mesocrystalline materials consisting of nanocrystal subunit alignment with the same crystallographic orientation have a potential application as active materials for lithium ion battery (LIB) electrodes. In this study, a topochemical process was developed to synthesize mesocrystalline CoTiO3/TiO2 nanocomposites using a layered titanic acid H1.07Ti1.73O4 (HTO) precursor. The H2O2 treatment of HTO caused more Co2+ intercalation into the interlayer by the H+/Co2+ exchange reaction and the formation of a sandwich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The mesocrystalline materials consist of oriented nanocrystals, in which the Li + migration is relatively fast. 28,29 As shown in Fig. 8(e), when Li + migrates from a Mn 2 O 3 or MnTiO 3 nanocrystal to the next Mn 2 O 3 or MnTiO 3 nanocrystal with the same orientation in the mesocrystalline material, the migration distance in the interface passage will be shorter compared with that of a Mn 2 O 3 or MnTiO 3 nanocrystal with random orientation in the polycrystalline material.…”
Section: Electrochemical Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The mesocrystalline materials consist of oriented nanocrystals, in which the Li + migration is relatively fast. 28,29 As shown in Fig. 8(e), when Li + migrates from a Mn 2 O 3 or MnTiO 3 nanocrystal to the next Mn 2 O 3 or MnTiO 3 nanocrystal with the same orientation in the mesocrystalline material, the migration distance in the interface passage will be shorter compared with that of a Mn 2 O 3 or MnTiO 3 nanocrystal with random orientation in the polycrystalline material.…”
Section: Electrochemical Performancementioning
confidence: 99%
“…[24][25][26][27] Furthermore, we have synthesized mesocrystalline MTiO 3 /TiO 2 (M = Co, Ni) nanocomposites from M 2+ ionexchanged layered titanates and demonstrated that the mesocrystalline MTiO 3 /TiO 2 nanocomposites can provide a short distance for charge transport and efficient Li + immigrating passage for Li + insertion/extraction reactions, which results in an enhanced specific charge-discharge capacity. 28,29 However, to the best of our knowledge, the study on the Li + insertion/ extraction reaction of mesocrystalline Mn 2 O 3 in LIBs has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Copyright 2018 Elsevier B.V. (c) Schematic diagram of Li + migration passage in CoTiO 3 mesocrystalline material. Reproduced from ref . Copyright 2021 American Chemical Society.…”
Section: Application Of Layered Titanatementioning
confidence: 99%
“…The mesocrystalline CoTiO 3 /TiO 2 nanocomposite exhibits a much larger reversible capacity than that of polycrystalline CoTiO 3 . 37…”
Section: Introductionmentioning
confidence: 99%
“…The mesocrystalline CoTiO 3 / TiO 2 nanocomposite exhibits a much larger reversible capacity than that of polycrystalline CoTiO 3 . 37 In this paper, firstly we studied the exfoliation reaction of H 2 O 2 -HTO and found that it can be exfoliated into H 2 O 2 -HTO nanosheets for the first time and the reaction is much quicker than that of the original HTO. The exfoliated H 2 O 2 -HTO nanosheets can be used to synthesize a polycrystalline NiTiO 3 / TiO 2 nanocomposite with high NiTiO 3 content.…”
Section: Introductionmentioning
confidence: 99%